Movable Antenna Enabled Interference Network: Joint Antenna Position and Beamforming Design - Wang, Honghao; Wu, Qingqing; Chen, Wen (IEEE wireless communications letters, 2024)
This letter investigates the utility of movable antenna (MA) assistance for the multiple-input single-output (MISO) interference channel. We exploit an additional design degree of freedom provided by MA to enhance the desired signal and suppress interference so as to reduce the total transmit power of interference network. To this end, we jointly optimize the MA positions and transmit beamforming, subject to the signal-to-interference-plus-noise ratio constraints of users. To address the non-convex optimization problem, we propose an efficient iterative algorithm to alternately optimize the MA positions via successive convex approximation method and the transmit beamforming via second-order cone program approach. Numerical results demonstrate that the proposed MA-enabled MISO interference network outperforms its conventional counterpart without MA, which significantly enhances the capability of inter-cell frequency reuse and reduces the complexity of transmitter design.